Antioxidant properties of water-soluble polysaccharides prepared by co-culture fermentation of straw and shrimp shell - Lyu, Yongmei; Wang, Mian; Zhang, Yiwen; Zhang, Xiaoyang; Liu, Xiaochen; Li, Fengwei; Wang, Dujun; Wei, Ming; Yu, Xiaohong (Frontiers in Nutrition, 2022)
Herein, we present a method for producing water-soluble polysaccharides (WSPs) by co-culture fermentation of straw and shrimp shells. The chitin-degrading strain was isolated and genotypically identified as the non-pathogen Photobacterium sp. LYM-1 in this study. Photobacterium sp. LYM-1 and Aureobasidium pullulans 2012 could coexist without antagonism. WSPs concentrations were higher in co-culture fermentations of Photobacterium sp. LYM-1 and A. pullulans 2012 (PsL/AP-WSPs) compared to monocultures (PsL-WSPs and AP-WSPs). FTIR was used to examine the polysaccharide properties of three WSP fractions. The monosaccharide compositions of three WSPs fractions were primarily composed of mannose, ribose, glucosamine, glucose, galactose, and arabinose with varying molecular weights and molar ratios according to HPLC analysis. PsL/AP-WSPs showed better scavenging effects on DPPH, ABTS, and OH free radicals, demonstrating the application potential of PsL/AP-WSPs from straw and shrimp shells. The maximum yield obtained under optimum conditions (fermentation time of 6 days, temperature of 31°C, inoculum concentration of 10% (w/v), and inoculum composition of 2:1) was 5.88 ± 0.40 mg/mL, based on the PsL/AP-WSPs production optimization by orthogonal design. The results suggest that an environmentally friendly approach for WSPs production from agro-food wastes straw and shrimp shells was developed.